Analysis of susceptibility to landslides in the basin of river Llaminchán (Cajamarca, Peru) - Villacorta, Sandra (2007)
The Llaminchan basin is located in the Western Cordillera of northern of Peru, within the Cajamarca region. The analysis using Geographic Information Systems of the mapping and inventory of slope movements, the topography, litology, hydrogeology applied to the Llaminchan Basin, allows obtaining the map of susceptibility to slope movements. It is show that the zones with greater susceptibility are to the northeast of San Pablo, the southern fl ank of the Callancas Hill, the northern sector of Santa Ana, the high area of Pueblo Libre-El Naranjo zone, and the zone between Chilete and the Paredones mine. This information will be presented to the authorities and population of the region that include the Llaminchan basin for their application in the territorial planning and the plans of prevention by natural disasters.